Analysis Of Leading Sector In Solok Regency - Zulfi, Muhammad Ramadhan; Pohan, Fawwaz Muhammad Zakli; Surbakti, Sinarta Putra P. (Politeknik Keuangan Negara STAN, 2023)
One of the fundamental bases for assessing the development of a country is by using Gross Domestic Product (GDP). At the regional level within a country, development is calculated using Gross Regional Domestic Product (GRDP). Kabupaten Solok is one of the well-known districts for its agricultural, forestry, and fisheries sectors, particularly in terms of rice cultivation. The purpose of this research is to identify the leading sectors and analyze sectoral shifts in Kabupaten Solok. The study utilizes secondary data on the GRDP of 17 sectors in Kabupaten Solok from 2017 to 2021. The research method employed is quantitative, using analytical tools such as Location Quotient, Dynamic Location Quotient, and Shift Share. The results of this research show that Kabupaten Solok does not yet have a leading sector based on the LQ and DLQ analyses. However, it has identified four sectors that exhibit rapid growth and competitiveness. The government's role is crucial in developing the economy based on the conditions of each sector. For future research, it is expected to delve deeper into the subject by utilizing input-output tables to examine the interrelationships between sectors in more detail